Efficacy and Safety of Plasma Exchange with Albumin Replacement as a Therapy for Amyotrophic Lateral Sclerosis. (August 2022) - Obat, Dennis Okumu; Stevanovic, Mirjana; Andrews, Catherine; Mondou, Elsa; Szczepiorkowski, Zbigniew; Barceló, Miquel; Woodward, Michael Ken; Ribó, Nuria; Liang, Wei; Stommel, Elijah; ,
Background: Neuroinflammation is being increasingly recognized as a key factor in the pathogenesis of amyotrophic lateral sclerosis (ALS). A therapeutic approach for ALS using plasma exchange with albumin replacement (PE-A) has been proposed to remove antibody complexes, inflammatory mediators, and toxins to decrease neuronal damage caused by inflammation.Methods: In this pilot study, 15 patients underwent 24 weeks of PE-A with 5% albumin and their revised ALS Functional Rating Scale (ALSFRS-R) scores and Forced Vital Capacity (FVC) were tracked for 48 weeks to evaluate the efficacy of PE-A as a therapy for ALS.Results: There was a statistically significant decline of ALSFRS-R scores as well as FVC (%) throughout the study. A post hoc comparison with clinically matched control patients showed no statistically significant difference. Likewise, no significant differences were found when the rate of ALSFRS-R decline in the PE-A-treated patients was compared to the European Medicines Agency (EMA) guideline estimate of a −1 point/month decrease in untreated patients. However, 50% of the PE-A-treated patients showed a slow rate of decline of < −0.8 points/month. PE was safe and well tolerated in ALS patients.Conclusion: In conclusion, results of this study indicated that PE-A performed in this manner was safe but showed a considerable heterogeneity in the response to treatment when it comes to slowing the ALS deterioration, with no overall clinical benefit. Further investigation focused on the characterization of ALS patients suitable for PE-A therapy is warranted.Registration: ClinicalTrials.gov ID: NCT02872142.